Comparative transcriptomic and metabolomic analyses reveal the delaying effect of naringin on postharvest decay in citrus fruit - Zeng, Jiaoke; Chen, Chuying; Chen, Ming; Chen, Jinyin (Frontiers in Plant Science, 2022)
Naringin exhibits antioxidant capacity and can partially inhibit pathogens in many horticultural products, such as citrus fruit; however, the effects of naringin on the storage quality and mechanisms that regulate senescence in citrus fruit have not been comprehensively analyzed. In this study, exogenous naringin treatment was found to significantly delay citrus fruit disease, decreasing the H2O2 content, increasing the antioxidant capacity and maintaining the quality of the fruit. Metabolomic analysis of citrus peel indicated the vast majority (325) of metabolites belonging to flavonoids. Moreover, the auraptene, butin, naringenin, and luteolin derivative levels within the phenylpropanoid pathway were significantly higher in the naringin-treated fruit than in the control fruit. Transcriptomic analysis also revealed that twelve genes in the phenylpropanoid and flavonoid biosynthesis pathways were significantly upregulated. Further analysis with a co-expression network revealed significant correlation between these differential genes and metabolites. Additionally, MYC and WRKY, screened from the MAPK signaling pathway, may contribute to naringin-induced disease resistance. In conclusion, naringin treatment can efficiently delay decay and maintain the quality of citrus fruit, mainly by promoting metabolites accumulation, and upregulating differentially expressed genes in phenylpropanoid and flavonoid biosynthesis pathway. This study provides a better understanding of the regulatory mechanisms through which naringin delays citrus fruit decay and maintains fruit quality.